2003
DOI: 10.1038/sj.bjc.6600824
|View full text |Cite
|
Sign up to set email alerts
|

Oral mucositis and selective elimination of oral flora in head and neck cancer patients receiving radiotherapy: a double-blind randomised clinical trial

Abstract: Mucositis is an acute inflammation of the oral mucosa because of radiotherapy and/or chemotherapy. All patients receiving radiotherapy in the head and neck region develop oral mucositis. The aim of this study was to analyse the effects of selective oral flora elimination on radiotherapy-induced oral mucositis, in a double-blind, randomised, placebo-controlled trial. Sixty-five patients with a malignant tumour in the head and neck regions to be treated with primary curative or postoperative radiotherapy partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
1
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 19 publications
0
59
1
10
Order By: Relevance
“…Amphotericin B is a polyene antifungal, often used intravenously for systemic fungal infections. Although initial pilot studies suggested the potential efficacy of this combination, subsequent larger well-controlled studies clearly demonstrated that topical use of PTA did not prevent OM or reduce its severity [76,77,79,83]. In addition, a well-controlled, multicenter, double-blind RCT examined the effect of a lozenge containing bacitracin, clotrimazole, and gentamicin (BCoG) for the prevention of radiation-induced OM in 137 H&N cancer patients.…”
Section: Combination Antimicrobial Lozenge or Pastementioning
confidence: 99%
“…Amphotericin B is a polyene antifungal, often used intravenously for systemic fungal infections. Although initial pilot studies suggested the potential efficacy of this combination, subsequent larger well-controlled studies clearly demonstrated that topical use of PTA did not prevent OM or reduce its severity [76,77,79,83]. In addition, a well-controlled, multicenter, double-blind RCT examined the effect of a lozenge containing bacitracin, clotrimazole, and gentamicin (BCoG) for the prevention of radiation-induced OM in 137 H&N cancer patients.…”
Section: Combination Antimicrobial Lozenge or Pastementioning
confidence: 99%
“…However, given its richness and diversity and its role in local inflammatory diseases, the potential of oral microflora to affect the course of mucositis seemed likely. Adding to this thinking was the finding over 50 y ago of shifts in the oral flora in response to chemotherapy (Peterson et al 1987;Reynolds et al 1989;Peterson 1990;Spijkervet et al 1991;Ruescher et al 1998;Stokman et al 2003;Napenas et al 2010;de Mendonca et al 2012;Laheij et al 2012). Consequently, numerous antimicrobial strategies have been studied as interventions for mucositis.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, numerous antimicrobial strategies have been studied as interventions for mucositis. Some have included the administration of systemic antibiotics (selective decontamination), whereas others have tested topical antibacterial therapies (Wijers et al 2001;Stokman et al 2003;Giles et al 2004). None have been successful.…”
Section: Introductionmentioning
confidence: 99%
“…Non-randomised trials reported about 30 to 40% reduction in stomatitis for patients, who followed a daily preventive protocol with chlorhexidine (0.2%) [19]. In a randomised clinical trial [23] preventive antimicrobial medication did not reduce the incidence of mucositis and is not recommended in the prophylactic setting.…”
Section: Radiation Induced Mucosal Injury Of the Oral Cavity And Headmentioning
confidence: 99%
“…Furthermore in these cells activation of transcription factors such as NF kappa B leads to the up-regulation of genes that modulate apoptosis processes. Direct and indirect epithelial stem cell deaths result in a loss of repopulation capacity and support mucosal surface damage [23,24].…”
Section: Radiation Induced Mucosal Injury Of the Oral Cavity And Headmentioning
confidence: 99%